Learning Outcomes in Functional Academics of Children with Special Needs in Inclusive school and Special school - Ranjan, Rajiv; Meena, O.P.; Meena, Meenakshi (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
The objective of this study was to find out the learning outcomes in functional academics of CWSN in inclusive schools and special schools at primary level. In this descriptive survey research, purposive sampling technique was used for selection of CWSNs i.e. visual impairment, hearing impairment and intellectual disabilities. Out of 78 CWSNs, 39 CWSNs were selected from Varanasi and Lucknow district of Uttar Pradesh however 39 were from Ajmer and Jaipur district of Rajasthan. The age group of samples was between 7 to 12 years. A tool on Learning Outcomes in functional Academics for CWSNs was developed and the items were presented under three domains- Languages, Mathematics and Environmental Studies. Reliability was established with the other developed tool in the area of special/inclusive education. The data was collected from 12 schools of Rajasthan and 14 schools of Uttar Pradesh. One-way ANOVA and t test were conducted. The findings of the research study are presented with tables and graph. The two important findings of this project are the difference in total mean scores of CWSNs studying in Special and Inclusive schools is found statistically non-significant and the difference in mean scores achieved by the three groups (VI/HI/ID) was not significant in language and environmental science; however, the difference in total score of HI and ID was significant.